Curriculum Reforms (Reviews/Revisions) and Innovative Research for Sustainable Development in Modern Africa: The Kenyan Experience - Kafu , Patrick (African Journal of Education,Science and Technology (AJEST), 2017)
Curriculum development, reforms (reviews/revisions) and research activities are expected developments in education and society. Though complex and education-packed in nature, these processes are required for promotion of quality in education. They are normally highly professional and academic activities that require specialized expertise. These processes usually provide opportunity for generating and nurturing creativity and innovativeness in members of the society. In other words, curriculum reviews/revisions indicate the purpose of the study and innovative research are the basis of initiating, developing and propagating the desired cultural practices in education and society. Besides, the two processes serve as agents of change in the society. That is, they mould the character of the society. In view of the above discussion, the present paper is designed to examine the relationship between curriculum reforms, innovative research and sustainable development. The role of these processes in spurring sustainable development in modern Kenya, the impact of the processes of curriculum and innovative research on sustainable development in modern Kenya, strategies for harnessing curriculum reforms (reviews/revisions) and innovative research for sustainable development in Kenya, the challenges of these processes of curriculum reforms and innovative research on initiating and promoting sustainable development in modern Kenya and the contributions of sustainable development to development and sustenance of curriculum reforms (reviews/revisions) and innovative research in modern Kenya. It is hoped that through the narrative that follows, new and more rigorous inertia will emerge in Kenya to embrace the culture of conducting curriculum reviews/revisions in a more professional and innovative manner than the case is at present.